Two cities : the political thought of American transcendentalism - Malachuk, Daniel S. (American political thought., 2016)
"This is an exploration of the political thought of the American transcendentalists focusing on Emerson, Thoreau, and Fuller. They were writing at a time when the American state was thought of as sacred, the two cities of Augustine, the City of God and the City of Man, combined as one. Indeed the Augustinian metaphor was a powerful one, frequently invoked in this period. American republican democracy in the City of Man enabled citizens through their participation in the state to achieve something close to the spiritual status of the City of God. The transcendentalists, with their emphasis on the importance of individual freedom, did not accept this analysis, according to Daniel Malachuk. They looked at American democracy and saw much that did not support individual pursuit of goodness nor a society that approached the status of the City of God. For example, the continued existence of slavery hardly fit with a godly place. Malachuk argues that the separation between the City of God and the City of Man remains important to transcendentalists who thought that individuals needed to be given space by the state to pursue their individual development"--